The effects of physical exercise on anxiety symptoms of college students: A meta-analysis - Lin, Yanru; Gao, Wei (Frontiers in Psychology, 2023)
Objective: This study aimed to evaluate the effect of an exercise intervention on improving and alleviating anxiety symptoms in college students with a meta-analytical approach. Methods: PubMed, Embase, the Cochrane Library and other databases were used to search for RCTs on interventions for physical exercise or aerobic exercise in college students with anxiety symptoms. Stata software, version 16.0, was applied sequentially for traditional meta-analysis, subgroup analysis, and publication bias analysis. Results: A total of 9 papers were included. The total literature effect (SMD=-0.55, 95% CI=-0.76 to -0.35, Z=5.38 (p<0.001)) indicated that physical activity had a significant effect on alleviating anxiety. Subgroup analysis also showed that exercise interventions using aerobic exercise or yoga were effective in relieving anxiety (SMD=-0.39, 95% CI=-0.74 to -0.04; SMD=-0.76, 95% CI=-1.14 to -0.39). Conclusion: Physical activity interventions were shown to have a positive effect on alleviating anxiety in college students. Aerobic exercise was found to be the optimal mode.